Vocabulary Learning Strategies of Japanese University Students (Journal of NELTA, 2021)
One of the many recent research interests in English language teaching in Japan is to develop student’s language skills through vocabulary learning, especially focusing on vocabulary learning strategies (VLSs). Our study examined the diﬀerent vocabulary learning strategies (VLSs) that proficient and non-proficient Japanese university students used to accomplish the learning tasks in the English language classrooms. It also sought to find out the significant diﬀerence between the two groups of students in vocabulary learning strategy use. The findings revealed that as many non-proficient students as proficient students used the same various VLSs in their English language classes. There were significant diﬀerences found between the two groups of students in their use of VLSs, specifically in four kinds of VLSs. These diﬀerences in VLSs use included social, memory, cognitive and metacognitive VLSs. In fact, there were instances when non-proficient students used VLSs more than proficient students. Implications for EFL as well as further research directions are discussed.